Rewriting the world order: China's footprint on the credit crisis and international affairs - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
Tired of reading conventional theories to what caused the recent financial crisis? How about a theory that places the blame on China, for a change? Giles Chance, author of “China and the Credit Crisis”, dances between the fine lines as he gives a fresh spin on the crisis, blind Western policymakers, a global currency and the world order that is to come as the "China effect" dominates familiar Western models of capitalism, politics and diplomacy.